The Development of Participatory Counseling Model in Controlling Dengue Mosquito Larvae in Palembang - Aseptianova, Aseptianova; Zalili, M. (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Dengue fever is a disease that threatens and disturbs  people, because it causes the patients die in a few days. Various of efforts have been done by the government, started from the  termination of the disease transmission vector, mosquito larva eradication, fogging,  larvacida providing and  counselling abou healthy to the population. This study aims to improve the cognitive and affective abilities of the population in eradicating mosquito larvae which cause dengue fever. Development research was done by implementing the participatory counseling model and the surveying method. Participatory extension model was implemented in three stages, 1) collecting information from citizens about the dengue fever patients, 2) consulting the expert, and 3) collaborating for joint  decision making. In the first year of survey to the public’s behavior towards the eradication of dengue mosquito larvae showed that, community was lacking  of  participation then  dengue mosquito larvae was under control, so the dengue disease was always be in the community.It was proved from the high population of mosquito larvae and the result of the conducted research The same results in the second year, the dengue mosquito larvae population was still relatively high. The development of a conseling participatory  model gave significant  influence to increase the cognitive, affective ability and population’s behaviour, also increase and active role in controlling the population of  masquito larvae  In the third year,of the study  population density of mosquito larva was medium .The result of the research after the participatory extension model was conducted showed that there was score improvement. Mosquito larvae controlling behaviour was higher than the cognitive and affective mosquito larvae control abilities . So, it could be concluded that , the cognitive abilities of mosquito larva control and ability of affective control mosquito larvae can significantly improve the mosquito larvae behavioral control .Keywords: counseling, participatory, dengue, mosquito larvae